Pitiful rooftop solar uptake in sunny South Africa: A policy, funding and service delivery perspective - McKay, Tracey; Hendricks, Donavan (Frontiers in Sustainable Cities, 2022)
Despite rolling blackouts, high electricity prices, a favorable climate and the size of the South African economy, rooftop photovoltaic (PV) solar products have low levels of middle-income residential market penetration. This study sought to establish the reasons for this. It was found, firstly, that households opt rather for demand side management (DSM) tools such as energy-efficient lamps or inverters. Secondly, they switch to gas (at least for cooking) or a generator rather than solar. This is because rooftop PV is expensive, in part due to costly batteries and inverters, but also as support measures such as feed-in tariff funding, tax rebates and subsidies are non-existent. In addition, South African banks are reluctant to finance rooftop PV, as return on investment (ROI) is extremely long term, and there are few, if any, bank-accredited PV suppliers. There is also no political pressure on banks to provide attractive PV financing. Furthermore, middle-income consumers struggle to understand PV technology and do not trust the suppliers thereof. For instance, rooftop PV companies seldom market themselves or their products adequately, and most do not sell PV with a maintenance service plan or offer credit. It is recommended that rooftop PV companies work with banks offer innovative, cost-effective modular PV packages, and build their brand to create a relationship of trust with the community to increase sales.